1998
DOI: 10.1016/s0924-9338(98)80019-9
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of register-based schizophrenia diagnoses in a genetic study

Abstract: In order to assess the accuracy of schizophrenia diagnoses for genetic studies, we identified all schizophrenia patients (n = 492) in an isolated community with a diagnosis of schizophrenia in the Finnish Hospital Discharge Register (HDR) between 1969-1991. For the accuracy study we identified a sample of 73 patients from registers with Diagnostic and Statistical Manual (DSM)-III-R for schizophrenia (codes 295.10, 295.30, 295.60, 295.90) (n = 62) or "schizophrenia spectrum" diagnoses (295.40, 295.70, 297.10, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 11 publications
3
59
0
Order By: Relevance
“…18 The diagnostic validity of the FHDR has been examined against DSM-III-R criteria and has been found to have excellent (92%-100%) specificity for diagnoses of schizophrenia. [19][20][21] We identified 928 individuals from the registers who had received a "295" diagnosis and who were born in Helsinki between 1951 and 1960. Child health cards were located for 486 of these individuals (52%) in the city archives, indicating that they had attended school in Helsinki; the remainder had attended school elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…18 The diagnostic validity of the FHDR has been examined against DSM-III-R criteria and has been found to have excellent (92%-100%) specificity for diagnoses of schizophrenia. [19][20][21] We identified 928 individuals from the registers who had received a "295" diagnosis and who were born in Helsinki between 1951 and 1960. Child health cards were located for 486 of these individuals (52%) in the city archives, indicating that they had attended school in Helsinki; the remainder had attended school elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…[38][39][40][41][42] The validity of the Finnish Hospital Discharge Register has been evaluated in several studies. [21][22][23][24] Virtually all inpatient hospital care periods in Finland are recorded in the register because the reporting is compulsory. The accuracy of most variables utilized in this study (personal and hospital ID numbers, age, sex, and dates of admission and discharge) is at least 95%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have concluded that the register has reasonably good validity for epidemiological research. [21][22][23][24] During the years 1972-2000, three versions of the International Classification of Diseases (ICD-8, -9, and -10) were used in Finland. The diagnosis related codes used in the identification of the study population were as follows: during ICD-8 (1972ICD-8 ( -1986 63,900 (hepatosis gravidarum, n ϭ 3,831)/63,901 (icterus gravis gravidarum, n ϭ 132)/63,909 (necrosis acuta et subacuta hepatis gravidarum, n ϭ 162); during ICD-9 (1987-1995) 6467A (hepatosis gravidarum, n ϭ 4,226)/6,467X (hepatopathia alia gravidarum, n ϭ 72); and during ICD-10 (1996-2000) O26.6 (intrahepatic cholestasis of gravidarum, n ϭ 2,081).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, previous validation studies have shown that the Hospital Discharge Register is able to capture nearly all persons with schizophrenia, schizotypal and delusional disorders. (44,45) Although all AD diagnoses were clinically verified according to a standard protocol, one limitation is that the diagnoses were probable AD rather than definite AD. However, the validity was improved by the practice that diagnoses were assessed by two independent specialists in clinical practice, and further evaluation was done in the SII according to the predefined criteria.…”
Section: Limitationsmentioning
confidence: 99%